Does Eliminating Extraordinary Items Impact the Usefulness of Accounting Information? - Chi , Yu-Ho (Journal of Accounting and Finance, 2021)
On January 9, 2015, the Financial Accounting Standards Board (FASB) approved Accounting Standards Update (ASU) 2015-01, which eliminates the required reporting of extraordinary items in an entity’s income statement. My analyses provide evidence regarding whether the usefulness of information in the financial statements is improved or reduced if no extraordinary items are to be reported. The results of my study suggest that while the change in reporting of extraordinary items does not completely eliminate its usefulness in explaining P/E ratios, the failure of firms to not report extraordinary items does significantly reduce the ability to explain cross-sectional differences in P/E ratios.